If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -3y = -3 Solving -2x + -3y = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. -2x + -3y + 3y = -3 + 3y Combine like terms: -3y + 3y = 0 -2x + 0 = -3 + 3y -2x = -3 + 3y Divide each side by '-2'. x = 1.5 + -1.5y Simplifying x = 1.5 + -1.5y
| 7=2(p-3) | | y=-3(9)+4 | | 8x+4x+3+6=3x+3+8x | | 2/3t-3=1 | | 6n^2-7n-5=0 | | -7x+5=x^2-11x-7 | | 82-5x=22 | | 7+2x+7x=-65 | | (125x^10)^-1/6 | | -2(2b+3)+(5b-9)=0 | | 2n-7=3n-3 | | 5x+7-3(x+1)=9x+6 | | 5(x)-12=53 | | 13(-12)+10+x=11 | | 8-4y=5 | | 2sinx-2=0 | | h^2+3h-29=0 | | 265=25x+39.0625 | | z/14=3 | | 15x=10+10x | | 16(v+4)-4v=4(3v+3)-14 | | x+(31+x)+(-37+3*x)=569 | | 13-12+10+x=11 | | -4(-15)/14-(-6) | | Y=40+0.80 | | 3x^2-11x=8-14 | | 40+0.80y= | | 40+0.8= | | 4(x+5)=30 | | 861=2 | | 861=1 | | 666=3 |